Characteristic features of an active polar filament pushing a load - Prabhakar Maurya, Shalabh Kumar Anand, Sunil Pratap Singh (SciPost Physics)
We present the structural and dynamical behavior of an active polar filament that is pushing a load using overdamped Langevin dynamics simulations. By varying the bending rigidity and the connectivity between the filament and the load, we smoothly transition the boundary condition of the filament from pivoted to clamped. In the clamped state, the load remains strongly aligned with the filament, whereas in the pivoted state, the load is free to rotate at its attachment point. Under the pivoted boundary condition, the active polar filament buckles and exhibits various fascinating dynamical phases, including snake-like motion, rotational motion, and helical conformations. However, under the clamped boundary condition, the helical phase disappears, and the filament attains either an extended or a bent conformation. The transition from the extended state to the helical phase is characterized using a global helical order parameter in the parameter space of active force and a physical quantity associated with the boundary condition. We have obtained various power laws relating the curvature radius of the helical phase, effective diffusivity, and rotational motion of the monomers to the active force. Furthermore, we demonstrate that the filament’s effective diffusivity in the helical phase exhibits a non-monotonic dependence on the active force: it initially increases linearly but decreases sharply at high active force strengths.